2009
DOI: 10.1177/1046496409332928
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Reasoning, Confirmation Bias, and Illusory Transactive Memory

Abstract: Teamwork is important in medicine, and this includes team-based diagnoses. The influence of communication on diagnostic accuracy in an ambiguous situation was investigated in an emergency medical simulation. The situation was ambiguous in that some of the patient's symptoms suggested a wrong diagnosis. Of 20 groups of physicians, 6 diagnosed the patient, 8 diagnosed with help, and 6 missed the diagnosis. Based on models of decision making, we hypothesized that accurate diagnosis is more likely if groups (a) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 66 publications
2
94
0
2
Order By: Relevance
“…Another study investigated the influence of ambiguous information on team function and clinical reasoning (49). Resuscitation teams were confronted with a patient undergoing penicillin-induced anaphylactic shock; however, the patient also reported pain due to a failed attempt to insert a central venous catheter, which could indicate a tension pneumothorax.…”
Section: Human Errors and Adverse Eventsmentioning
confidence: 99%
“…Another study investigated the influence of ambiguous information on team function and clinical reasoning (49). Resuscitation teams were confronted with a patient undergoing penicillin-induced anaphylactic shock; however, the patient also reported pain due to a failed attempt to insert a central venous catheter, which could indicate a tension pneumothorax.…”
Section: Human Errors and Adverse Eventsmentioning
confidence: 99%
“…Observers of postoperative handovers found that much critical information (eg, allergies or intraoperative problems) was not communicated from OR doctors to ward nurses 26 27. There is also evidence suggesting that specific techniques to improve information sharing can improve clinical management, such as, in the high acuity setting, declaring an emergency and sharing information about a crisis with the team28 or ‘thinking aloud’—verbalising observations and decision-making processes to the team to share your mental model 29…”
Section: Introductionmentioning
confidence: 99%
“…However, research on teamwork has also shown that teams do not like explicit coordination; they prefer to coordinate implicitly 41. Whereas teams of novices may have no choice other than to coordinate explicitly, team of experts may be at higher risk for developing team phenomena such as illusionary transactive memory23 or avoidance of overt discussions about teamwork 42. Although this result needs to be validated in further studies, ideally incorporating performance outcomes, it highlights the importance of teamwork training in healthcare emphasising direct communication and leadership,43 44 particularly for expert teams.…”
Section: Discussionmentioning
confidence: 99%